2014
DOI: 10.5664/jcsm.4204
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Infants with Obstructive Sleep Apnea

Abstract: Comorbidities in infants with OSA differ from those of older children. Based upon the comorbidities identified in our study population, it appears that appropriate management of infants with OSA requires a multidisciplinary approach involving genetics, gastroenterology, pulmonology, otolaryngology, neurology, and general pediatrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 22 publications
1
57
0
2
Order By: Relevance
“…17 Likewise, the suggested prevalence of OSA in our comparison group (7%) is similar to the frequency (5.7%) of OSA that is reported to occur in the general population. 30 It cannot be determined whether the association is a causal one, and the possibility of interfering variables cannot be discounted. The association appears to be a real one, with our study mirroring previous work.…”
Section: Discussionmentioning
confidence: 99%
“…17 Likewise, the suggested prevalence of OSA in our comparison group (7%) is similar to the frequency (5.7%) of OSA that is reported to occur in the general population. 30 It cannot be determined whether the association is a causal one, and the possibility of interfering variables cannot be discounted. The association appears to be a real one, with our study mirroring previous work.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] Several authors recently summarized current information on normal values for SDB in PSG done neonates and young infants. [59][60][61][62][63][64]65 They found that: (1) apneas are common in normal infants this age; (2) the majority of apneas observed are central in type (70-80%) and typically last ≥ 3 but < 10 sec; (3) central apneas are commonly seen in REM sleep, after a sigh breath or a body movement, and during transition from wakefulness to sleep; (4) apneas lasting > 10 seconds are usually mixed apneas; and (5) periodic breathing is common typically averaging < 5% of sleep time for infants 1 and 3 months of age.…”
Section: Limited Reference Values For Scoring Respiratory Events In Imentioning
confidence: 99%
“…Корреляция собственно тяжести апноэ во сне была обнаружена для нейромышечных аномалий, недоношенности и генетических синдромов. У 86% детей имелось сочетание тех или иных состояний [4].…”
unclassified